THE FORMATION OF HUMAN CAPITAL AND ITS ROLE IN DEVELOPMENT FROM A PHILOSOPHICAL PERSPECTIVE (Scientific journal of the Fergana State University, 2026)
This article explores the concept of human capital as one of the fundamental notions in modern science, philosophy, politics, and economics. It emphasizes that human capital is not merely an economic resource, but also serves as a foundation for the development of the moral values and future of nations. The article analyzes the philosophical essence of the phenomena of “human” and “capital” within this concept, as well as various approaches to understanding human capital. Furthermore, through a theoretical analysis of its relation to the concepts of the human factor and human potential, it is revealed that the concept of human capital is a key instrument for increasing economic efficiency and promoting social progress.